Atrial flutter-related health care use and costs: An analysis of a nationally representative administrative claims database in the United States - Abhishek Deshmukh, MD; Maximiliano Iglesias, BE, MBA; Rahul Khanna, MBA, PhD; Tara Beaulieu, MIPH, PhD (Heart Rhythm O2, 2023)
Background: Atrial flutter (AFL) is a common arrhythmia associated with significant morbidity, yet the incremental burden of this condition has not been well documented. Objective: Using real-world data, we sought to evaluate the healthcare use and cost burden of incident AFL in the United States Methods: From 2017 to 2020, persons with an incident diagnosis of AFL were identified through Optum Clinformatics, a nationally representative administrative claims database of commercially insured individuals in the United States. We constructed 2 cohorts (AFL patient; non-AFL comparator) and used a matching weights method to balance covariates between cohorts. Using logistic regression and general linear models, 12-month all-cause and cardiovascular (CV)-related health care use (inpatient, outpatient, emergency room [ER] visits, and other) as well as medical expenditures were compared between the matched cohorts. Results: The matching weight sample sizes were 13,270 for AFL and 13,683 for the non-AFL cohorts. In the AFL cohort, ∼71% were at least 70 years of age, 62% identified as male, and 78% identified as White. The AFL cohort had significantly higher health care use, including all-cause (relative risk [RR] 1.14; 95% confidence interval [CI] 1.11–1.18) and CV-related ER visits (RR 1.60; 95% CI 1.52–1.70) compared with the non-AFL cohort. Mean total health care costs (per patient annually) were almost $21,783 (95% CI $18,967–$24,599) higher among patients with AFL compared to those without AFL ($71,201 vs $49,418, respectively; P <.001). Conclusion: Amidst the backdrop of an aging population, findings from this study draw attention to the importance of timely and adequate treatment of AFL.